Application of Photovoltaic Panels as Producers of Electrical Energy With IoT Technology Based on Programmable Logic Controller - Aryanto, Budi; Sanjaya, Bomo Wibowo; Sujaini, Herry; Panjaitan, Seno Darmawan; Yacoub, Redi Ratiandi; Miharja, Nata (ELKHA : Jurnal Teknik Elektro, 2024)
The process of converting solar cell electrical energy is a form of utilizing environmentally friendly alternative energy sources (renewable energy). The conversion system is in the form of PV panels that are installed in a location exposed to sunlight and unobstructed. Monitoring is carried out when the sun shines from morning to evening. The location of the panel is in the vehicle parking lot of the engineering faculty, while monitoring is carried out in the Control Laboratory of the Tanjungpura University Engineering Faculty, which is 300 meters away. Factors that determine the quality of PV panels are the system and dimensions. This shows that fluctuations in current (I), voltage (V) and power (P) need to be controlled so that load distribution and reserves can prevent reduced energy generation. Observation and control using Long Range Area (LoRa) radio transmission media connections, Internet of Things (IoT) and Programmable Logical Control (PLC) in real-time. Observation and test results show that energy generation has experienced an increase in temperature which has an impact on reducing power. Meanwhile, the effect of the distance between the installed panels produces an average delay of 7 milliseconds (midday conditions). Meanwhile, the Signal to Noise Ratio (SNR) value for data transmission is 30 dBm at the device frequency of 868.125 MHz. Baud rate 2400-9600 bps with a speed of 0.3 bps "“ 62.5 Kbps. The application of this system is a research novelty because it can determine and control the generation of electrical energy at minimum, maximum and optimum conditions with a certain distance between the observer and the installed panel.